HUBUNGAN OBESITAS DENGAN KADAR KOLESTEROL PADA MAHASISWA KEDOKTERAN UNIVERSITAS MALAHAYATI - Teguh Pribadi; Devita Elsanti; Andri Yulianto (Malahayati International Journal of Nursing and Health Science, 2019)
Background: At the time of hospitalization of children, they feel uncomfortable such as an anxiety. Statistics data base in 2010 in Indonesia reported that in 35 of 420 children has stress during hospitalization. However during hospitalization the children must be cooperate in treatment for recovery.Purpose: Knowing the influence of play therapy: origami and puzzles for reducingan anxiety to children at Pertamina Bintang Amin Hospital, Bandar Lampung-Indonesia 2018.Methods: Quantitative researchwith design used quasi-experimental. The study population was all patient at pediatric ward at Pertamina Bintang Amin Hospital, Bandar Lampung Indonesiawith 50 children as sampleand used instruments: Zung Self-Rating Scale (ZSRAS) and Tailor Manifest Anxiety Scale (T-MAS).The statistical analysis used an independent T test.Results: Finding significane different of the total score of anxiety before and after play therapy (before play therapy: origami and puzzle were 20.2and20.7) and (after play therapy: origami and puzzle were 14.9 and 12.7). The total score rates was descrease of 5.27 in origami therapy and of 8.0 in puzzle therapy with p-value of 0.000.Conclusion: There was differences effect in both of play therapy: origami and puzzle to reducing an anxiety.It is suggestions to management hospital to provide play therapy such as origami and puzzle as an alternative therapy to reduce anxiety to the children due to hospitalization and thus supporting the healing process.